2017
DOI: 10.1007/s00167-017-4625-4
|View full text |Cite
|
Sign up to set email alerts
|

Stenotic intercondylar notch type is correlated with anterior cruciate ligament injury in female patients using magnetic resonance imaging

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 29 publications
5
54
0
1
Order By: Relevance
“…Because of the low prevalence of PCL avulsion fracture, screening only to determine the risk of sustaining a PCL avulsion fracture would likely not be cost e cient. However, several studies on the relationship between morphological measurements and traumatic diseases of the knee including ACL injury [6][7][8][9][10], ramp lesion of meniscus [11], and tibial spine avulsion fractures [12], PCL injury [13,14], have already been conducted, and more risk factors have been associated with knee-related sports injuries. All of these risk factors could be combined as a menu to nd and help patients at risk for different types of knee injury [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the low prevalence of PCL avulsion fracture, screening only to determine the risk of sustaining a PCL avulsion fracture would likely not be cost e cient. However, several studies on the relationship between morphological measurements and traumatic diseases of the knee including ACL injury [6][7][8][9][10], ramp lesion of meniscus [11], and tibial spine avulsion fractures [12], PCL injury [13,14], have already been conducted, and more risk factors have been associated with knee-related sports injuries. All of these risk factors could be combined as a menu to nd and help patients at risk for different types of knee injury [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, several studies on the relationship between morphological parameters and traumatic diseases of the knee have already been conducted. Many studies have found different relationships between measurements of knee geometry and anterior cruciate ligament (ACL) injury, such as stenotic intercondylar notch type [6], intercondylar notch volume [7], medial tibial slope [8], lateral tibial slope [9], and tibial slopes (both bony and meniscal) [10]. Similarly, Song et al reported that increased medial meniscal slope was associated with greater risk of ramp lesion of the meniscus in noncontact ACL injury [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, many surveys have determined a narrow intercondylar notch to be a risk factor for the ACL rupture in adults (Smith et al, 2012;Li et al, 2018;Shen et al, 2018;Taneja et al, 2018) and children (Dorizas and Stanitski, 2003;Domzalski et al, 2010). These studies were based on recent imaging methods, magnetic resonance imaging (MRI) in particular, due to the excellent image quality with no radiation exposure, which is crucial in the pediatric population (Bouras et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many methods of notch size measurements on imaging have been described. 2,[8][9][10] However, most methods have been used to study the relationship of notch size to ACL injury, and few have tried to reproduce arthroscopic measurements. Zeng et al 11 performed a meta-analysis of 16 studies assessing the correlation between intercondylar notch size and the risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%